Intermediate wheatgrass seed size and moisture dynamics inform grain harvest timing. Issue 1 (10th December 2021) - Heineck, Garett C.; Schlautman, Brandon; Law, Eugene P.; Ryan, Matthew R.; Zimbric, Joseph W.; Picasso, Valentin; Stoltenberg, David E.; Sheaffer, Craig C.; Jungers, Jacob M.
Abstract: Intermediate wheatgrass (IWG) [ Thinopyrum intermedium (Host) Barkworth & D. R. Dewey subsp. intermedium ] is being domesticated as a perennial grain crop. Advanced grain‐type IWG populations display variability in key physiological parameters related to seed development, making it difficult to determine grain harvest timing. A quantitative literature review of cool‐season grasses informed the modeling of IWG field trial data. Results revealed that multiple species exhibited a consistent multiphase dry‐down pattern from anthesis to a stabilized moisture content, which often included a rapid dry‐down phase that presaged maximum seed dry matter and gave insight into the relationship between floret shatter and maximum seed yield. A field trial was conducted at three locations in which IWG spikes were repeatedly sampled postanthesis and divided into three fractions to measure physiological patterns over growing degree days (GDDs). Similar to literature review results, IWG demonstrated a rapid dry‐down phase that started when seed moisture content was between 44.7 and 52.8% and decreased at a rate of −0.12 to −0.20% GDD −1 during this phase. At all locations, florets began shattering before seeds reached maximum dry matter, which resulted in reduced floret site utilization. Seed from distal fractions reached 95% dry matter 135 GDDs earlier than seed from basal fractions, while basal seeds were 21% larger than distal seeds. Timing of maximized seed yield per spike ranged from 530 to 701 GDDs after mid‐anthesis provided a starting point for estimating optimum IWG seed harvest timing under high and low shattering conditions and also supports the importance of repeated measurement of seed moisture to pinpoint optimal harvest time. Core Ideas: Intermediate wheatgrass (IWG) grown for grain lacks research for modeling yield components. A quantitative literature review of perennial grass seed crops informed IWG model hypotheses. Perennial grasses exhibited multiphase moisture loss that regulated maximum seed dry matter. The onset and magnitude of shattering in IWG influenced the timing of maximum seed yield.